2019
DOI: 10.1002/acm2.12745
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife® icon CBCT offers improved localization workflow for frame‐based treatment

Abstract: Object: The purpose of this study was to compare two methods of stereotactic localization in Gamma Knife treatment planning: cone beam computed tomography (CBCT) or fiducial. While the fiducial method is the traditional method of localization, CBCT is now available for use with the Gamma Knife Icon. This study seeks to determine whether a difference exists between the two methods and then whether one is better than the other regarding accuracy and workflow optimization.Methods: Cone beam computed tomography wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…suggested that CBCT improves traditional methods by defining stereotactic coordinates at the time of patient docking into the Gamma Knife couch and seems to be more reliable. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…suggested that CBCT improves traditional methods by defining stereotactic coordinates at the time of patient docking into the Gamma Knife couch and seems to be more reliable. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Expecting the known uncertainty discussed in this article, we might add a margin, such as 1 mm, for the treatment of a G‐framed patient to reduce the problematic warnings. Alternatively, we can stop the use of the MR/CT indicator box for coordinate definition by using CBCT even with G‐framed patients as proposed by Duggar et al 15 Yet, another solution is to enable the LGP to adjust the head position using the geometrical translation and rotation data obtained by co‐registration of CBCT and plan reference image sets with the G‐framed patient as done with all masked patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous prior studies on the IU have been conducted, including general descriptions of commissioning experiences, 1 assessment of the accuracy 2 , 3 and quality assurance 4 (QA) of the image guidance system. Past studies on the previous PU model have assessed the stability of the definition of stereotactic coordinates using a stereotactic head frame, 5 commissioning and QA of the automatic positioning system, 6 QA of the PU beam accuracy, 7 , 8 and evaluation of the dose calculation software 9 and a secondary dose calculation system.…”
Section: Introductionmentioning
confidence: 99%